Fundamental principles of positron emission tomography (PET) 1 - Mawlawi, Osama (Henry Stewart Talks, 2010)
Principles of PET imaging, The PET process, Positron decay, Nuclide production, Decay schemes of 18-F, Image reconstruction, Different views when using PET scanners, The process of image formation in details, Annihilation, Detector/photomultiplier design, Energy trigger, measurement and qualification, Event positioning, Coincidence assessment of singles events, Steps involved in coincidence assessment, Coincidence acceptance angles (Transverse & Axial), Coincidence timing comparison, Overall LOR determination process, LOR data storage, Sample sinograms, Detector assembly, Direct and cross planes, Axial sampling and slice sensitivity, Michelograms, Further improvement in sensitivity, 2D and 3D, Inter-plane septa, Type of recorded events, Two ways of measuring randoms in PET, Randoms estimation, Scatter and its extent in PET images, KCPS vs. activity concentration, Scatter correction, Power of PET by quantification, Normalization, Dead-time, Decay correction, Geometric correction, Attenuation measurement, Calculated attenuation correction, Segmented attenuation correction, Effect of attenuation correction on PET image, CT based attenuation correction, Calibration, Factors affecting image resolution, Detector size, Depth of interaction, Resolution improvement, Positron range, Non co-linearity, Linear and angular sampling, Image matrix, Reconstruction filter
Reviewed at 2020/09/11, Updated at 2022/07/14